KAJIAN PENGGUNAAN PUPUK SUBSIDI DAN NON SUBSIDI DI DESA KEPALA SUNGAI, KECAMATAN SECANGGANG, KABUPATEN LANGKAT - Rahmi Dwi Handayani Rambe; Rahmad Setia Budi (Universitas Islam Sumatear Utara, 2022)
Fertilizer is one of the important inputs in increasing the productivity of food crops, so that its existence and utilization has a strategic position. One of the policies in the procurement of fertilizers is fertilizer subsidies. Fertilizer subsidies have long been implemented with various policies that follow it, such as policies on fertilizer procurement, distribution of fertilizers and supervision of subsidized fertilizers. The problem faced is that local people do not know which are subsidized and non-subsidized fertilizers. So that with this extension, the Kepala Sungai community can find out the type and method of obtaining the fertilizer. This PKM activity has added insight from the local community in knowing which fertilizers are subsidized and non-subsidized, although there are some things that still need to be improved for the progress of agriculture in the future. In Indonesia, the distribution of fertilizer subsidies is currently still constrained. These deviations include incomplete RDKK data collection, distribution of subsidized fertilizers to unauthorized parties, lack of distribution volume that causes a shortage of fertilizers, procurement and distribution of subsidized fertilizers by the fertilizer industry, obstacles in calculating fertilizer subsidies, and supervision of subsidized fertilizer distribution. Most of the deviations in the implementation of subsidized fertilizer program policies occur at the retailer, distributor and producer level as well as the weak mechanism for monitoring the implementation of subsidized fertilizers. Aspects of transparency and information disclosure in the implementation chain of the subsidized fertilizer policy program are also still weak. The strategy for distributing or distributing subsidized fertilizers in Indonesia can be implemented through several distribution alternatives.